Minimum emission pathways to triple Africa’s cereal production by 2050 - Ittersum, Martin K. van; Hijbeek, Renske; Berge, Hein F.M. ten; Loon, Marloes P. van; Boogaard, Hendrik L.; Tesfaye, Kindie (2019)
Cereals play a central role in food security in sub-Saharan Africa (SSA), where they account for approximately 50% of caloric intake and total crop area. Cereal demand in the region is projected to nearly triple between 2015 and 2050 due to rapid population growth (van Ittersum et al. 2016). Increases in cereal yields are very slow in most SSA countries and agricultural area expansion is still an important means to keep up with the growing demand, causing losses of forests or grasslands, thereby reducing carbon stocks. At the same time the Paris Conference of the Parties (COP21) Agreement aims to keep global warming below 2 °C or even 1.5 °C by 2100. SSA has already seen a continuous increase in emissions from agriculture-driven deforestation between 1990 and 2015. Yet, intensification, i.e. higher yields per hectare with sufficient and judicious use of inputs, will also lead to higher emissions per unit area because of the required fertiliser use.